Making the transition from pharmacy student to pharmacist: Australian interns' perceptions of professional identity formation. (2nd November 2014) - Noble, Christy; Coombes, Ian; Nissen, Lisa; Shaw, Paul N; Clavarino, Alexandra
Abstract: Objectives: The experience of transitioning from university to practice influences professional identity formation. It is unclear how this transitioning experience influences pharmacy interns' professional identities. This study aims to examine pharmacy interns' perceptions of their transition from university to the workplace and the influence this had on their pharmacist identities. Methods: A qualitative approach using in-depth interviews was adopted for this study. Fifteen interns (community and hospital) from one school of pharmacy in Australia were interviewed. Questions were asked about the nature of their current intern role, their university experiences, how they saw themselves as pharmacists and their perceptions of the transition to practice. Key findings: The interns interviewed entered the workplace valuing patient-focused aspects of practice and contributing to patient care. The nature of work meant there were limited opportunities to enact these aspects of their professional identities. The interns were challenged by interactions with patients and doctors, and experienced difficulties reconciling this with their university-derived professional identities. Also, the interns lacked the confidence and strategies to overcome these challenges. Some were exploring alternative ways of being pharmacists. Conclusions: This paper argues that graduates' experience of the transition to practice was challenging. This was due to nascent professional identities formed in university and a lack of workplace experiences enabling patient-centred practices. The interns' formation of professional identities was highly responsive to the context of work. To facilitate the development of Australian patient-centred pharmacy practice, supporting professional identity formation should be a focus within pharmacy education.